Symptom improvement in adenomyosis patients after ultrasound guided microwave ablation or uterine artery embolization, A randomized controlled pilot study - Gudny Jonsdottir; Erika Lantz; Marie Beermann; Maria Paschou; Helena Kopp Kallner; Klara Hasselrot (PLoS ONE, 2026)
Introduction The objective of this study was to investigate alleviation of adenomyosis symptoms after microwave ablation (MWA) and uterine artery embolization (UAE) in a small pilot study. Material and methods 20 premenopausal women with symptomatic adenomyosis were included at Danderyd Hospital, Sweden, from June 2020 to February 2023. Patients were randomized to MWA or UAE. The primary outcome was symptom severity score (SSS) at 6 months post treatment evaluated through the UFS-QoL questionnaire. The secondary outcomes were comparison of: health related quality of life (HR-QoL/UFS-QoL), Pictorial Bleeding Assessment Chart (PBAC), dysmenorrhea on a numerical rating scale (NRS), uterine volume, hemoglobin, Ca-125, prolactin and Anti Müllerian hormone (AMH), duration of hospitalization, use of pain medication and acceptability. As exploratory outcomes, we evaluated postoperative pain and return to daily activities. Clinical trials number NCT04209127. Results There was no significant difference in primary outcome between the groups: SSS decreased within the MWA group from 69 to 44 (p=0.007), and within the UAE group from 88 to 47 (p=0.067). Quality of life increased significantly in the MWA group from 27 to 79 (p=0.002) and in the UAE group from 13 to 67 (p=0.013). Dysmenorrhea decreased in both groups; NRS from 6 to 1 (p=0.008) in the MWA group and from 9 to 4 (p=0.02) in the UAE group. The MWA group had significantly shorter hospitalization (0 days vs 3, p=0.004), and quicker return to daily activities (3 days vs 14, p=0.005), compared to the UAE group. No serious adverse events occurred. Conclusion In this small pilot trial, we had low power to detect differences between groups. Both treatments resulted in a significant decrease of symptoms related to adenomyosis. Postoperative recovery seems superior after MWA, in line with previous trials. Further investigations regarding MWA for adenomyosis are needed.